Literature Review: Curcumin Alternative Therapy For Breast Cancer - Nurayuni, Tiara (Jurnal EduHealth, 2024)
Breast cancer is a serious disease that affects millions of people worldwide every year. Risk factors include gender, age, family history, and genetic factors. Although there are treatment methods such as surgery, radiation, and chemotherapy, breast cancer management often brings various physical, social, psychological, and financial problems for patients. Therefore, alternative treatments like the use of herbal plants, particularly compounds like curcumin, have been researched as potential anticancer agents with minimal side effects. The aim of this study is to explore in depth the potential of curcumin in breast cancer. This article is compiled from various databases, including Pubmed and Google Scholar, using the keywords "curcumin, breast cancer, anticancer." The journals sought were published between 2015 and 2024, and five journals were identified as relevant to the topic for further discussion. Based on literature studies, several mechanisms of curcumin against breast cancer include the regulation of protein signaling pathways, inhibition of cancer cell proliferation, induction of apoptosis, and reduction of drug resistance. Additionally, curcumin can also inhibit metastasis and increase the sensitivity of cancer cells to other therapies. The combination of curcumin with other drugs like tamoxifen can enhance its effectiveness in treating breast cancer. Based on this, it can be concluded that curcumin can be used as an alternative therapy for breast cancer through its various mechanisms.